Constitutional triumphs, constitutional disappointments : a critical assessment of the 1996 South African Constitution's local and international influence - Roux, Theunis; Dixon, Rosalind (Cambridge, United Kingdom ; New York, NY: Cambridge University Press, 2018)
"The 1996 South African Constitution was promulgated on 18th December 1996 and came into effect on 4th February 1997. Its aspirational provisions promised to transform South Africa's economy and society along non-racial and egalitarian lines. Following the twentieth anniversary of its enactment, this book, co-edited by Rosalind Dixon and Theunis Roux, examines the triumphs and disappointments of the Constitution. It explains the arguments in favor of the Constitution being replaced with a more authentically African document, untainted by the necessity to compromise with ruling interests predominant at the end of apartheid. Others believe it remains a landmark attempt to create a society based on social, economic, and political rights for all citizens, and that its true implementation has yet to be achieved. This volume considers whether the problems South Africa now faces are of constitutional design or implementation, and analyses the Constitution's external influence on constitutionalism in other parts of the world"--
Machine generated contents note: 1. Introduction Rosalind Dixon and Theunis Roux; 2. Mission in progress: towards an assessment of South Africa's Constitution at 20 Catherine O'Regan; 3. The performance of socio-economic rights in the South African Constitution David Bilchitz; 4. Proceduralism's promise: the Constitutional Court, social and economic rights and democracy Steven Friedman; 5. Corruption, the rule of law and the role of independent institutions Heinz Klug; 6. Violence against women in South Africa: constitutional responses and opportunities Beth Goldblatt; 7. Toward reparative transformation: revisiting the impact of violence against women in a post-TRC South Africa Andrea Durbach; 8. The constitutional goal of transforming education: the South African Constitutional Court in comparative perspective Julie C. Suk; 9. Race, inclusiveness and transformation of legal education in South Africa Penelope Andrews; 10. The contribution of the South African Constitution to Kenya's Constitution Jill Cottrell Ghai and Yash Ghai; 11. Multi-Stage constitution-making: from South Africa to Chile? Joel Colon-Rios; 12. A cure for coups: the South African influence on Fijian constitutionalism Coel Kirkby; 13. Policing democracy: the influence of South Africa's post-Apartheid security arrangements on police oversight under Kenya's 2010 Constitution Richard Stacey; 14. The diffusion of South African-style institutions? A study in comparative constitutionalism Charles Manga Fombad; 15. Constitutionalism, legitimacy, and public order : a South African case study Aziz Z. Huq; 16. South African social rights jurisprudence and the global canon: a revisionist view David Landau.
Includes bibliographical references and index.
Keywords: South Africa; Constitutional law -- South Africa; Equality before the law -- South Africa; Civil rights -- South Africa; South Africa -- Economic policy; South Africa -- Politics and government -- History